2015
DOI: 10.1115/1.4032146
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary Flow of a Thin Nanoliquid Film Over an Unsteady Stretching Sheet

Abstract: The two-dimensional flow of a thin nanoliquid film over an unsteady stretching sheet is studied under the assumption of planar film thickness when the sheet is heated/cooled along the stretching direction. The governing equations of momentum, energy are solved numerically by using finite difference method. The rate of film thinning decreases with the increase in the nanoparticle volume fraction. On the other hand, thermocapillary parameter influences the film thinning. A boundary within the film is delineated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As a result, the increasing viscosity resists the fluid motion along the stretching direction leading to the slowdown of the film thinning process. 96…”
Section: Code Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the increasing viscosity resists the fluid motion along the stretching direction leading to the slowdown of the film thinning process. 96…”
Section: Code Validationmentioning
confidence: 99%
“…In another study, Makinde & Animasaun 50 presented the MHD nanofluid on bioconvection flow of a paraboloid revolution with nonlinear thermal radiation and chemical reaction while Sandeep, 51 Reddy et al 52 and Ali et al 53 studied the heat transfer behaviour of MHD flows. Maity et al 54 analyzed thermocapillary flow of a thin Nanoliquid film over an unsteady stretching sheet. Furthermore, different studies on the flow and heat transfer behaviour as well as entropy generation for different non-Newtonian fluids under difference internal and external conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The surface tension plays an important role on the free liquid surface. Other studies about thermocapillary effect on a thin film can be found in [35][36][37][38].…”
Section: Stretching Sheetmentioning
confidence: 99%
“…However, the results presented using HAM were for the value of the Prandtl number which is not suitable for water-based nanofluids. Recently, Maity et al (2016) investigated thermocapillary effect on flow and heat transfer of thin nanoliquid film. Unlike all the works mentioned, they considered the full Navier-Stokes quations.…”
Section: Introductionmentioning
confidence: 99%